Faktor Penyebab Rendahnya Partisipasi Guru dalam Penyusunan Aksi Nyata pada Aplikasi PMM - Krishannanto, Deddy; Fajrie, Nur; Fathurohman, Irfai (Jurnal Prakarsa Paedagogia, 2024)
This study aims to identify the factors that cause low teacher participation in preparing PMM concrete actions and efforts to overcome the problem of low teacher participation in preparing concrete actions. The results of the study show the factors that cause low teacher participation in making PMM concrete actions are teachers are constrained by time to study the topic to make concrete actions, teachers need infrastructure and technology to support teachers in making concrete actions, require perseverance and high concentration, teachers do not understand the details/guidelines of concrete actions, lack of collaboration with colleagues. Efforts made by schools to increase teacher participation in making PMM concrete actions include socialization, training, and good practices in the school community, improving and upgrading infrastructure to support teacher activities in making concrete actions, using PMM applications in learning activities, making special schedules for teachers to collaborate in making PMM concrete actions, uploading concrete action results that pass validation to social media.